Proceedings of the 16th International Symposium on Management (INSYMA 2019) 2019
DOI: 10.2991/insyma-19.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of good corporate governance on dividend policy

Abstract: This study aims to determine the effect of good corporate governance on dividend policy. The study used a sample of all non-financial companies listed on the Indonesia Stock Exchange. T h i s research also used control variables of firm size, profitability, leverage, firm growth, and free cash flow. The results show that the variables of good corporate governance, firm growth and free cash flow had a positive significant effect on the dividend payout ratio. Meanwhile, the variable firm size, leverage, and prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
4
2
Order By: Relevance
“…Financial performance significantly influences the firm value. These results are consistent with the research of Gunawan et al (2019). This result explains that when a company announces that its performance improves, shareholders' response increases the price.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Financial performance significantly influences the firm value. These results are consistent with the research of Gunawan et al (2019). This result explains that when a company announces that its performance improves, shareholders' response increases the price.…”
Section: Discussionsupporting
confidence: 91%
“…Investors will respond to companies with good performance in the form of an increase in share pricesvice versa. Companies with satisfactory performance will be able to grow in the future (Gunawan et al, 2019). Novita et al (2016) showed that the essential variable influencing stock price is performance measured by earnings per share.…”
Section: The Effect Of Dividends and Financial Performance On Firm Valuementioning
confidence: 99%
“…(Saputra, 2018) show that, independent board of commissioners is the core of corporate governance assigned to ensure the implementation of corporate strategy, to maintain management in managing the company and to require the enforcement of accountability. This research of this study are different from the results of research conducted by (Zulfikar et al, 2017), (Andriana & Panggabean, 2017) and (Farida et al, 2018) which prove that independent commissioner has no effect on financial performance. (Andriana & Panggabean, 2017) states that the existence of an independent commissioner is only to meet the regulations set by the government.…”
Section: The Effect Of Independent Commisioner On Financial Performancecontrasting
confidence: 99%
“…The results of study performed by (Mahrani & Soewarno, 2018), (Saputra, 2018) and (Bintara, 2019) which states that independent commissioner has effect on financial performance. These results are different from the study performed by (Andriana & Panggabean, 2017), (Zulfikar et al, 2017) and (Farida et al, 2018) which stated, that independent commissioners has no effect on financial performance.…”
Section: Introductioncontrasting
confidence: 87%
See 1 more Smart Citation